De la Commune aux massacres d’Arménie - Sylvie Brodziak (Études Arméniennes Contemporaines, 2016)
George Clemenceau experienced physical and moral violence several times in his lifetime, but a tragic event proved particularly devastating. On March 18, 1871, when he was Mayor of Montmartre, he was a helpless witness to the murder of Generals Lecomte and Thomas by an angry crowd, an episode that affected him for the rest of his life. While he was capable of evoking violence in his speeches, the writer that he was to become was unable to write any fiction whose object was, for example, workers’ strikes or the battlefield. Yet the one event that pushed him to narrate extreme violence were the Armenian Massacres. In 1896, in a now famous preface, Clemenceau dared to write ‘cries and blood,’ as if to suggest that when humanity is denied, only writing the massacre could warn his contemporaries and the next generations.